2022
DOI: 10.1080/01652176.2022.2102688
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of adipose-derived stromal vascular fraction in veterinary practice

Abstract: Adipose tissue-derived stromal vascular fraction (AdSVF) comprises a heterogeneous cell population, including the multipotent mesenchymal stem cells, hematopoietic stem cells, immune cells, endothelial cells, fibroblasts, and pericytes. As such, multipotent adipose tissue-derived mesenchymal stem cells (AdMSCs), are one of the important components of AdSVF. Commonly used techniques to harvest AdSVF involve enzymatic or non-enzymatic methods. The enzymatic method is considered to be the gold standard technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 152 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that various growth factors in the PRP matrix can promote cell proliferation. In addition, the porous structure of the 3D printing scaffold also provides sufficient space for cell proliferation (Bai et al, 2020a;Sharun et al, 2021). The limited number and survival rate of transplanted cells has always been a challenge for stem cell therapy for bone defects (Whitely et al, 2018).…”
Section: Biocompatibility Cell Proliferative Activity and Cell Morpho...mentioning
confidence: 99%
“…Previous studies have shown that various growth factors in the PRP matrix can promote cell proliferation. In addition, the porous structure of the 3D printing scaffold also provides sufficient space for cell proliferation (Bai et al, 2020a;Sharun et al, 2021). The limited number and survival rate of transplanted cells has always been a challenge for stem cell therapy for bone defects (Whitely et al, 2018).…”
Section: Biocompatibility Cell Proliferative Activity and Cell Morpho...mentioning
confidence: 99%
“… 65 In some instances, adipose-derived SVF (adSVF) is used as a first step for obtaining high cellular yield for subsequent culture expansion of adMSCs. 66 In other instances, SVF is offered as a sole therapy. Traditionally, adSVF is obtained by the enzymatic digestion of fat.…”
Section: Challenges With Feline Stromal Cell Production and Usementioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) exhibit paracrine effects, immunomodulation, and differentiation capabilities contributing to tissue repair (Bist et al 2021;Peer et al 2022;Sivanarayanan et al 2023). Encouraging results from preclinical studies have paved the way for clinical trials exploring stem cell-based therapies (Sharun et al 2020;Bist et al 2021;Peer et al 2022;Sharun et al 2022;Sivanarayanan et al 2023). However, standardization of protocols, ethical considerations, and long-term safety assessments remain crucial challenges.…”
Section: Introductionmentioning
confidence: 99%